1991
DOI: 10.1097/00006123-199104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Second operation after the failure of previous resection for epilepsy

Abstract: We present our surgical experience with second operations in 15 patients with recurrent intractable partial seizures after resection for epilepsy. The interval from the first operation until the first recurrence of seizures ranged from 1 day to 7 months (mean, 62 days). The interval between the first and second operations ranged from 3 months to 12 years (mean, 38 months). Detailed video-electroencephalographic interictal and ictal recording was performed in all patients (invasive electrodes were used in 11 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 0 publications
5
38
3
1
Order By: Relevance
“…Several authors suggested that amygdala and hippocampus removal is essential in achieving a good surgical outcome (8)(9)(10)12,13,21,22). In a trial randomizing the extent of hippocampus resection while maintaining controlled lateral temporal resection in 70 patients, Wyler et al (9,13) showed that complete hippocampectomy (to the level of the colliculus) was associated with significantly better seizure control (69% seizure free at 1 year vs. 38%) than partial hippocampectomy (to the anterior edge of the cerebral peduncle).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors suggested that amygdala and hippocampus removal is essential in achieving a good surgical outcome (8)(9)(10)12,13,21,22). In a trial randomizing the extent of hippocampus resection while maintaining controlled lateral temporal resection in 70 patients, Wyler et al (9,13) showed that complete hippocampectomy (to the level of the colliculus) was associated with significantly better seizure control (69% seizure free at 1 year vs. 38%) than partial hippocampectomy (to the anterior edge of the cerebral peduncle).…”
Section: Discussionmentioning
confidence: 99%
“…Despite reasonable seizure control achieved with temporal structure resections, there still remains a 20-60% recurrence rate, varying in onset from the perioperative phase to several years after surgery (9)(10)(11)(12). Potential reasons for failures include nonfocal or bitemporal lobe epilepsy, unresected lesion, perilesional or postsurgical gliosis, extratemporal lesions, or diffuse cerebral disease, as may be present after meningitis or encephalitis (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because the PoleStar N-10 has a built in neuronavigational system, we often used its "optical wand" to locate the temporal horn of the lateral ventricle after the brain had shifted, rendering standard neuronavigational systems inaccurate. The role of IMRI also may be critical for reoperations when the surgical anatomy is distorted and the risk of complications slightly higher (11). Another potential use for IMRI would be to determine intraoperatively the extent of division of the corpus callosum after callosotomy, which has already been reported by Nimsky et al (39).…”
Section: Imri and Epilepsy Surgerymentioning
confidence: 94%
“…As a result of depth-electrode studies, investigators have demonstrated ictal onsets arising not only from the anterior hippocampus but also from the posterior hippocampus, amygdala, and parahippocampal gyrus (5)(6)(7)(8). Studies using high-resolution postoperative magnetic resonance imaging (MRI) to correlate residual medial temporal lobe structures with outcome have demonstrated the impact of residual hippocampus and parahippocampal gyrus in recurrent seizures after medial temporal lobe resections (9)(10)(11)(12). Several retrospective and prospective studies also confirmed a higher seizurefree rate after a more extensive hippocampal resection, and many surgeons now perform a radical amygdalohippocampectomy as an integral part of their temporal lobe resections (13)(14)(15)(16).…”
mentioning
confidence: 99%